PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI INKLUSIF TERHADAP MUTU PENDIDIKAN DI SEKOLAH DASAR ISLAM TERPADUPADANG PARIAMAN - Hasibuan Nasrin; Hamdi Abdul Karim (Jurnal Manajemen Pendidikan, 2026)
Objective:. This study aims to analyze the partial and simultaneous effects of principal transformational leadership and inclusive organizational culture on educational quality in Integrated Islamic Elementary Schools (SDIT) in Padang Pariaman Regency. Methods: A correlational quantitative approach was applied involving 91 respondents of teachers and staff. Data were collected via Likert-scale questionnaires in April 2026 and analyzed using multiple linear regression via SPSS software. Results: Partial testing proved that transformational leadership (t = 6.584; p = 0.000) and inclusive organizational culture (t = 10.342; p = 0.000) have positive and significant effects on educational quality. Simultaneously, both variables significantly influence the outcome (F = 107.894; p = 0.000), with a combined contribution (R Square) of 71.0%, while the remaining 29.0% is influenced by other variables. Conclusion/Novelty: The novelty of this research lies in integrating inclusivity values into the organizational culture of regional-level faith-based private schools. Responsive leadership successfully transforms educator diversity into a collaborative asset to guarantee the quality of both the process and output of Islamic education.